Влияние дебиторской задолженности на финансовую устойчивость предприятия - Зубкова, В.И.; Мироненко, А.С. (Культура народов Причерноморья, 2013)
В статье раскрыта экономическая сущность дебиторской задолженности как фактора, который оказывает влияние на финансовую устойчивость предприятия. Рассмотрены и охарактеризованы этапы управления задолженностью, проанализированы основные финансово- экономические показатели, характеризующие деятельность малых предприятий Украины. Раскрыта необходимость проведения на предприятиях политики управления дебиторской задолженностью. Рассмотрены основные причины и последствия задолженности и определены мероприятия по процессу управления дебиторской задолженностью. Ключевые слова: дебиторская задолженность, управление дебиторской задолженностью, платежный кризис, устойчивость, платежеспособность. У статті розкрито економічну сутність дебіторської заборгованості як фактора, що справляє вплив на фінансову стійкість підприємства. Розглянуто та охарактеризовано етапи управління заборгованістю, проаналізовано основні фінансово-економічні показники, що характеризують діяльність малих підприємств України. Розкрито необхідність проведення на підприємствах політики управління дебіторською заборгованістю. Розглянуто основні причини і наслідки заборгованості та визначено заходи процесу управління дебіторською заборгованістю. Ключові слова: дебіторська заборгованість, управління дебіторською заборгованістю, платіжна криза, стійкість, платоспроможність. The article reveals economic matter of the accounts receivable e as a factor that affects the financial sustainability of an enterprise. Stages of debts management have been examined and described, main financial and economic indicators that define activities of small enterprices of Ukraine, have been analyzed. The article reveals the necessity of implementation of the politics of an accounts recievable management on the enterprises. It examines the main causes and effects of debts and specifies the measures of their management. Three types of credit politics of enterprise are considered in relation to the customers of products: conservative, moderate and aggressive. Worked out ways of effective management an account receivable of enterprises, taking into account features each of them. Certain basic directions of forming of politics of management an account receivable are with the aim of increase of financial firmness of enterprise. On the modern stage of development of country development of complex approach in relation to a management an account receivable on the stage of her forming and collection has a large practical value, that is why this fact predetermines the necessity of further research of control system by an account receivable. Keywords: accounts payable, accounts receivable management, payments crisis, stability, solvency.